Republic of San Marino : 2018 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for the Republic of San Marino. (IMF Staff Country Reports; Country Report, 2018)
This 2018 Article IV Consultation highlights that San Marino's economy rebounded in 2016, on the back of recovering domestic demand and important gains in employment. However, the growth momentum slowed in 2017 amid financial sector uncertainties around a sizable loss at the largest bank and a closure of a small bank. Only moderate growth is projected in the near and medium term. The economy is projected to grow at 1.3 percent in 2018, driven by domestic demand. Private consumption is expected to recover gradually, and an externally financed investment project will add a significant boost to investment, which otherwise lacks support from the deleveraging banking sector.